The use of authentic materials in the teaching-learning process in the Intermediate Intensive English I and Advanced Intensive English I at the English Foreign Language Department during the year 2014 - Cabezas Hernández, Breny Magalí; Calderón Vásquez, David Ernesto; Soriano Mármol, Rigoberto Antonio (2024)
In order to know if the use of authentic materials influences the speaking and writing performance in Teaching Learning Process while learning a new language, the researchers conducted the research project: "The use of authentic materials in the teaching learning process in the Intermediate Intensive English I and Advanced Intensive English I at the Foreign Language Department of the University of El Salvador during the year 2014" The researchers designed two tools, a questionnaire and an interview in order to identify as much as possible how the lack of authentic materials might affect the Teaching Learning Process for students in the previous mentioned levels in the department. To recognize the students who made use of these resources to improve their learning and which ones did not, the researchers administered some questionnaires and performed some interviews to confirm how important the use of these materials in Teaching Learning Process is. With all this information, the researchers organized the data in tables and represented it in graphs that facilitated the analysis and final interpretation of the results. At the end, the researchers provided conclusions and recommendations about the importance that the use of authentic materials stated above bring to the English level process regarding the writing and speaking skill